Medieval studies and the ghost stories of M.R. James - Murphy, Patrick J., 1977- (The Pennsylvania State University Press, 2017)
"Examines the ghost stories of writer and academic Montague Rhodes James (1862-1936). Focuses on the intersection between his scholarly work and his fiction, arguing that his two careers are intriguingly intertwined"--Provided by publisher